1, 2, 5‐Oxadiazole‐Based High‐Energy‐Density Materials: Synthesis and Performance. Issue 1 (8th November 2019) - Fershtat, Leonid L.; Makhova, Nina N.
Abstract: This Review covers the synthesis and performance of the most promising 1, 2, 5‐oxadiazole‐based high‐energy density materials (HEDMs). These materials comprise a 1, 2, 5‐oxadiazole subunit as a key structural motif linked to various acyclic explosophoric groups or to nitrogen‐rich and nitrogen‐oxygen azoles: 1, 2, 4‐triazole, tetrazole, 1, 2, 4‐ and 1, 3, 4‐oxadiazoles. Energetic alliances of two and more 1, 2, 5‐oxadiazole rings linked directly or through heteroatom spacers are also presented. Particular attention is devoted to the installation of different explosophores: nitro, nitramino, azo, azoxy, dinitromethyl, trinitroethyl moieties and their combination. Promising environmentally benign energetic materials with high detonation velocity and pressure, and outstanding insensitivity are summarized. Overall, the presented materials may be considered as next‐generation high‐performance energetic materials that are superior to commonly used traditional explosives (TNT, PETN, RDX, HMX). Abstract : High energy : Significant recent achievements in the design and synthesis of high‐energy density materials incorporating 1, 2, 5‐oxadiazole (furazan) or its N‐oxide (furoxan) motifs are described. Furazan and furoxan subunits are unique explosophores which provide an increase in density and enthalpy of formation of target high‐energy structures. Their combination explosophoric nitrogen‐oxygen functionalities and other motifs have become an important strategy to achieve powerful materials with excellent detonation performance.